Search and performance in ecosystems: The changing role of product architectures - Axel Zeijen; Luigi Marengo; Stefano Brusoni (Scuola Superiore Sant'Anna, Laboratory of Economics and Management (LEM), 2023)
A crucial assumption in organization theory is that product architectures form a stable basis on which firms make strategic choices, over a period of time. However, emerging digital technologies challenge this idea, by allowing firms to redesign architectures at will. In this paper, we explore this novel phenomenon, its effects, and its theoretical implications. We develop an NK model suitable for studying (i) variable interdependence structures between components and (ii) the dynamics of search and adaptation in ecosystems. We find that the possibility to redesign product architectures undercuts the stability on which vertical relationships are based. We distinguish two pathways through which firms can benefit from redesigning product architectures: by enhancing the fitness landscape (landscape redesigns) or by altering the conditions on which inter-firm coordination is based (ecosystem redesigns). The availability of these two pathways depends on a firm's positioning (vertical scope and location in the value chain). Our results shed light on the changing role of interdependence structures in ecosystems, the differential advantages of integration and specialization strategies, and the effects of digital technologies in both technical and organizational domains.
Keywords: I22; I23; O32; 330; Digital technologies; ecosystems; firms' boundaries